Bibliometric analysis of socially responsible investment: a systematic review in the field of education - Balıkçı, Hasan Celal; Alpsülün, Mustafa; Ermiş, Uğur Ferhat; Brika, Said Khalfa; Barut, Müzeyyen; Barut, Abdulkadir (Springer Nature, 2026)
This study examines the role of socially responsible investment (SRI) in education. Using bibliometric analysis and a systematic literature review, it was found that while SRI has received increasing attention over the years, studies focusing specifically on education are limited. The findings demonstrate that SRI has the potential to enhance students’ ethical awareness and foster a sense of social responsibility. The importance of educational institutions in raising responsible individuals for the future is emphasized, particularly through the development of SRI-focused curricula and projects. Furthermore, interdisciplinary research is required to address the existing gaps in this area. © The Author(s) 2026.
Keywords: Education; Ethical leadership; Social responsibility in education; Socially responsible investments (SRI); Sustainability